2012
DOI: 10.4103/0300-1652.104386
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of human immunodeficiency virus post exposure prophylaxis among Nigerian Family Physicians

Abstract: Background:To determine the level of awareness and knowledge of HIV postexposure prophylaxis (HIV PEP) and determinants of adequate knowledge among Family Physicians in Nigeria.Materials and Methods:This was a cross-sectional questionnaire-based survey conducted among 175 Family Physicians at two national conferences.Results:Majority (97.7%) of the respondents was aware of the concept of HIV PEP and 99.4% believed it was effective in preventing HIV transmission. Over two third of our respondents had been expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
31
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 16 publications
4
31
9
Order By: Relevance
“…16 In the present study most of the participants had NSI while recapping the needle and similar finding was observed in the study conducted by Yousafzai et al and bayappa reddy N et al 17,19 In the present study the most common factor influenced NSI was hasty work and similar finding was observed in the study conducted by Bayappa Reddy N et al 17 In our study all private practitioners had heard of HIV post exposure prophylaxis (PEP) and almost similar finding was observed by Patricia A et al (98%). 18 Our study observation is higher than the other studies conducted by C Ooi et al (68%) and Biniam Mathewos et al (48%). 20,21 In the present study 81% told HIV (PEP) is effective in preventing HIV transmission, which is lower than study conducted by Patricia A et al (99.4%).…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…16 In the present study most of the participants had NSI while recapping the needle and similar finding was observed in the study conducted by Yousafzai et al and bayappa reddy N et al 17,19 In the present study the most common factor influenced NSI was hasty work and similar finding was observed in the study conducted by Bayappa Reddy N et al 17 In our study all private practitioners had heard of HIV post exposure prophylaxis (PEP) and almost similar finding was observed by Patricia A et al (98%). 18 Our study observation is higher than the other studies conducted by C Ooi et al (68%) and Biniam Mathewos et al (48%). 20,21 In the present study 81% told HIV (PEP) is effective in preventing HIV transmission, which is lower than study conducted by Patricia A et al (99.4%).…”
Section: Discussioncontrasting
confidence: 56%
“…16,17 In a study conducted by Patricia A et al, 69.4% of the respondents reported history of needle stick injuries. 18 In the present study 47% had needle stick injury only once which is higher than the study conducted by yousafzai et al (26.7%) and lower than study conducted by fullerton et al (75.6%). 16,19 In the present study 42% had 2-5 times in the last one year and which is lower than study conducted by fullerton et al (21.9%).…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations